Development of soluble coffee substitute from velvet beans (Stizolobrum Deeringianum) - Borja, Carmencita Crispino (1981)
ABSTRACT This study aimed at developing a soluble coffee substitute from velvet beans (Stizolobium daeringianum) which could be utilized as coffee "stretchers" or as beverage itself for those who are against the stimulating effects of coffee. This was carried out by, first, determining optimum roasting time. Velvet beans were roasted at varying length of time: 15; 20 and 25 minutes. Optimum extraction method was, then determined testing 3 methods: boiling; percolating and steeping. the extract obtained from optimum extraction method was spray dried at two drying temperature ranges: 180-200°F and 201-220°F to determine the optimum spray drying temperature. During the three stages mentioned, products obtained were subjectively and objectively evaluated. Results of the study reveal that roasting 100 grams of velvet beans at 400-450°F for 20 minutes was optimum in terms of the color of the ground roast beans and the taste and general acceptability of its brew. Sensory evaluation indicted that boiling method gave a spray dried powder and brew which was most preferred, since its color and sensory characteristics and acceptability of its brew were more superior than the two other methods. Spray drying of extract using 2 drying temperature ranges revealed insignificant difference between samples. Results of the objective tests on the soluble coffee substitute reveal that % yield was only 7.5% and the moisture content was 2.0%. Powder had an ash content of .50%, 1% insoluble solids, bulk density of .39 grams per ml, poor solubility and a pH value of 6.8 upon reconstitution. Based on the sensory evaluation, soluble coffee substitute can be described to possess the following characteristics: between brown to dark brown in terms of color of the spray dried powder. With respect to the brew, it was voted as being dark brown to brown in color, having coffee to weak coffee aroma, has coffee to bitter taste and which was liked slightly to moderately.